2020
DOI: 10.1186/s43055-020-00309-9
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 disease: CT Pneumonia Analysis prototype by using artificial intelligence, predicting the disease severity

Abstract: Background Since the beginning of 2020, coronavirus disease has spread widely all over the world and this required rapid adequate management; therefore, continuous searching for rapid and sensitive CT chest techniques was needed to give a hand for the clinician. We aimed to assess the validity of computed tomography (CT) quantitative and qualitative analysis in COVID-19 pneumonia and how it can predict the disease severity on admission. Results One hundred and twenty patients were enrolled in our study, 98 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Assessment of 3-class severity (mild, moderate, severe) is crucial to determine the treatment route [14] and is well summarized in the WHO interim guidance on clinical management of COVID-19 2 . Some recent literature have shown chest CT to determine COVID-19 severity qualitatively and quantitatively with good correlation with clinical parameters [15][16][17]. Further, recent studies have also demonstrated that quantification of lung CT based severity can predict the short-term prognosis of COVID-19 [18,19].…”
Section: Review Of Literaturementioning
confidence: 94%
See 1 more Smart Citation
“…Assessment of 3-class severity (mild, moderate, severe) is crucial to determine the treatment route [14] and is well summarized in the WHO interim guidance on clinical management of COVID-19 2 . Some recent literature have shown chest CT to determine COVID-19 severity qualitatively and quantitatively with good correlation with clinical parameters [15][16][17]. Further, recent studies have also demonstrated that quantification of lung CT based severity can predict the short-term prognosis of COVID-19 [18,19].…”
Section: Review Of Literaturementioning
confidence: 94%
“…Sun et al using commercial software quantified a number of CT features including the percent lesion cover and the type of deposition to classify 84 patients into severe and non-severe categories with about 91% specificity and sensitivity [15]. On the other hand, Gouda and Yasin quantified CT features of 120 patients including percentage of high and low opacity and total lesion cover using a CT pneumonia analysis algorithm by Siemens Healthineers [16]. With the aid of AI-rad —an artificial intelligence based lesion detection tool they could classify mild and non-mild cases with a sensitivity of up to 90%.…”
Section: Introductionmentioning
confidence: 99%
“…The % opacity was also negatively correlated with SpO 2 . In a study using the same CT Pneumonia Analysis software, the opacity score, % opacity, volume of opacity, volume of high opacity, % high opacity and mean HU total were significantly higher in the moderate and severe groups compared to the mild group, while the total lung volume was significantly lower in the severe group compared to the mild group [14]. The results of our study also showed significant differences in % opacity and % of high opacity in univariate analysis, which is consistent with their results.…”
Section: Ct Pneumonia Analysis Displays Various Quantitative Valuesmentioning
confidence: 95%
“…The positive rate for CT imaging for the diagnosis of suspected COVID-19 patients was 88% vs. 59% by RT-PCR, and the sensitivity of CT increased to 97% based on positive RT-PCR results, confirming the role of CT as a primary tool for diagnosis [6]. Several studies have shown the ability of visual quantitative evaluation of CT images to predict mortality and severity with high consistency [7][8][9][10], and these scoring techniques are now applied to the risk prediction and severity evaluation of COVID-19 pneumonia using artificial intelligence (AI) [11][12][13][14]. In these AI-based approaches, the use of routine blood test results is still limited to a few studies.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation